Automatic Generation of Combinatorial Test Data - Zhang, Jian.; Zhang, Zhiqiang; Ma, Feifei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book reviews the state-of-the-art in combinatorial testing, with particular emphasis on the automatic generation of test data. It describes the most commonly used approaches in this area - including algebraic construction, greedy methods, evolutionary computation, constraint solving and optimization - and explains major algorithms with examples. In addition, the book lists a number of test generation tools, as well as benchmarks and applications. Addressing a multidisciplinary topic, it will be of particular interest to researchers and professionals in the areas of software testing, combinatorics, constraint solving and evolutionary computation.
Introduction to Combinatorial Testing -- Mathematical Construction Methods -- One Test at a Time -- The IPO Family -- Evolutionary Computation and Metaheuristics -- Evolutionary Computation and Metaheuristics -- Tools and Benchmarks -- Other Related Topics.
Keywords: Software engineering; Computer science—Mathematics.; Artificial intelligence; Software Engineering; Math Applications in Computer Science; Artificial Intelligence